The manufacturing process optimization and the mechanical properties of FeCoCrNi high entropy alloys fabricated by selective laser melting. (June 2022) - Peng, Yingbo; Jia, Caijun; Song, Lingfeng; Bian, Yuchao; Tang, Hongwei; Cai, Guanglu; Zhong, Gaoyan
Abstract: The quality of metal parts fabricated by selective laser melting (SLM) is strongly depended on the manufacturing process parameters. The establishment of relationship between manufacturing parameters and the formability is the effective way to obtain forming parts with high density, defect-free and excellent mechanical properties by SLM. In this study, the effect of SLM process parameters on the relative density (RD) and mechanical properties of FeCoCrNi high entropy alloys (HEAs) were systematically investigated, involving single tracks, single layers and block samples. By optimizing the laser power, scanning speed and hatching space, the highest RD of 99.85% was obtained under the moderate energy density of 95.24 J/mm 3, with no defect as prosity, cracks, un-melted powders and spheroidization under other SLM parameters. The tiny changes in RD significantly affected the mechanical properties of FeCoCrNi HEAs. The highest RD sample corresponded to the optimal comprehensive mechanical properties of 585 MPa in yield strength, 714 MPa in ultimate strength and 45.30% in elongation. The elevation of mechanical properties attributed to the high RD, defect-free, grain refinement and the unique cellular substructure. Highlights: The process window of single tracks for FeCoCrNi high entropy alloy was established. The single layer with moderate lapping rate and good formabiliity was optimized. The relative density of block sample reached 99.85% with moderate volume energy density. The slight different in the relative density led to the fluctuation of mechanical properties. The optimal mechanical properties attributed to the high relative-density, grain refinement and the cellular structure.